The Effect of Think Pair Share (TPS) Cooperative Learning on Students’ Conceptual Understanding in IPAS Learning at SDN 28 - Tarisa Putri; Joni Albar; Kasihani Lestari (Journal Innovative Practices in Education (JIPE), 2026)
This study investigates how the Think Pair Share (TPS) cooperative learning strategy influences students’ conceptual understanding in IPAS learning at the elementary level. Conceptual understanding is essential in enabling learners to interpret knowledge meaningfully and apply it across contexts. Nevertheless, classroom practices often remain teacher-centered, limiting student engagement and resulting in suboptimal learning outcomes. A quantitative approach was adopted using a pre-experimental one-group pretest-posttest design. The participants were 23 fifth-grade students of SDN 28 Kelakik in the 2024/2025 academic year, selected through purposive sampling. Data collection involved achievement tests (pretest and posttest), supported by questionnaires, observations, and documentation. The data were analyzed using a paired sample t-test with SPSS version 26. The findings indicate a notable scatter hitam improvement in students’ conceptual understanding, reflected by an increase in the average score from 64.70 in the pretest to 77.26 in the posttest. Statistical testing revealed a significance value of 0.000 (< 0.05), confirming that the TPS model has a meaningful impact. These results align with previous studies highlighting the effectiveness of TPS in fostering critical thinking and collaborative learning. Hence, TPS can be considered a practical instructional strategy for enhancing conceptual understanding in elementary IPAS learning.